Pengaruh Flow Experience, Escapism dan Habit Terhadap Adiksi Media Sosial Tiktok di Jakarta - Keiza Zeta Lazuardi; Ryna Parlyna; Adnan Kasofi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine how technological factors through flow experience generated by the algorithm, personal factors in the form of escapism driven by scrolling design, and social factors that shape usage habits through the streak feature contribute to social media addiction among TikTok users. Data were collected through an online survey using Google Forms. Participants in this study were active TikTok users residing in the Jakarta area, aged 18 to 28 years, who use TikTok daily and have consistently utilized the streak feature. The data were analyzed using Structural Equation Modeling based on Partial Least Squares with SmartPLS 4.0, involving a total of 160 respondents. The results indicate that flow experience has a positive and significant effect on social media addiction, escapism shows a positive but non-significant effect on social media addiction, and habit is proven to have a positive and significant effect on social media addiction. These findings suggest that deep engagement shaped by the For You Page (FYP) algorithm immerses users in continuous use without conscious interruption; the internal drive for emotional escape through TikTok’s infinite scrolling design is not strong enough to form addiction when not reinforced by other mechanisms; and usage patterns formed through streak gamification operate at an automatic and repetitive level, thereby strengthening users’ attachment to the platform.